Development of Learning Modules for the Tarbiyah Islamiyah Program at The Integrated Islamic Senior High School Wahdah Islamiyah Palopo - Rachman, Anita; Sahraini, Sahraini; Kartini, Kartini (Universitas Cokroaminoto Palopo, 2023)
The aim of this writer's research was to produce a product in the form of a learning module in the Islamic tarbiyah program at the Integrated Islamic Senior High School Wahdah Islamiyah Palopo. This study uses research and development (RandD). This research developed an existing product, namely mawad (a set of consumables used by murabbi/murabbiyah in the Islamic tarbiyah program at the Integrated Islamic Senior High School Wahdah Islamiyah Palopo. The subjects of this study were murabbi and murabbiyah at the Integrated Islamic Senior High School Wahdah Islamiyah Palopo, totaling three people (one murabbi and two murabbiyah). and class X SMAIT Wahdah Islamiyah will be 31 people, class XI will be 25 people and class XII will be 21. The research object is mawad (collection of materials) tarbiyah Islamiyah marhalah ta'rif 1. including: observation/observations, interviews, literature studies, questionnaires and documentation.This quantitative analysis technique was used to analyze the research data this time which presents the results of product development in the form of the tarbiyah marhalah ta'rif 1 module. Data were obtained from research instruments/tools obtained through validation by three experts and a questionnaire answering teachers and students at the Integrated Islamic Senior High School Wahdah Islamiyah Palopo. The findings in this study are that in implementing the Islamic tarbiyah program, murabbi/murabbiyah in various regions use mawad (collection of material) whose material is discussed in general for all groups. Currently, murabbi/murabbiyah, especially at the Integrated Islamic Senior High School Wahdah Islamiyah Palopo, do not yet have a module where the material has been separated according to the time period for which the material must be completed so that the material is not completed according to the specified time period.